Comparison between Sublingual and Vaginal Misoprostol for Induction of Labour in Primigravida - Ghimire, Sailaja; Sharma, Deepanjali; Dhakal, Samjhana; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To compare the outcome and side effects of administration of sublingual misoprostol with vaginal misoprostol for induction of labour and cervical ripening. Methods: It was a hospital based comparative study which was carried out in 120 patients in each group of sublingual and vaginal route of misoprostol induction from August 2016 to February 2017 at Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu. Patients with Bishops score <6 were subjected for Misoprostol 25 μg (for maximum 2 doses) 6 hours apart. Results were analyzed using SPSS 21 taking p-value <0.05 as statistically significant. Results: The mean change in Bishops score after 6 hours of misoprostol was statistically signifi cantly (p=0.001) in sublingual group in comparison to vaginal group. The diff erence in augmentation rate was not statistically signifi cant (p= 0.811). The mean time interval from drug administration to delivery was almost similar in both groups. The indications for cesarean section were similar in both the groups, the most common being fetal distress, (67.33% in sublingual and 58.065% in vaginal group). In terms of maternal and neonatal outcome there was no difference. Conclusions: Sublingual route results in significant changes of Bishop’s score as compared to vaginal route. It was also significantly better in terms of fetal outcome. However, both routes appeared similar in terms of maternal outcome.